Numerical Investigation On The Effect Of Wind Pressure On Skillion Roof Using Computational Fluid Dynamics (Cfd) - Bahari, Mohamad Taqif Saipol (Universiti Sains Malaysia, 2022)
Presently, windstorm event has been occurring frequently due to unpredictable weather conditions that is caused by climate change. Many studies have been conducted to determine the effect of wind pressure on the roof profile of houses, this includes low-rise and rural houses. The studies conducted were mainly on certain roof types such as gable and hip when there are many other roof shapes and sizes that are available in the country such as skillion roof. Moreover, code of practice for wind loading only considers design for gable, hip and shed roof shapes. This study investigates the pressure coefficient distribution of skillion roof along the profile of low-rise house and the net pressure acting across overhang roof. Computational Fluid Dynamics method using RNG k-ε turbulence model was used as the method has the ability to accurately predict the flow field. The results showed that the presence of overhang roof on the flat roof model did not affect the magnitude of the coefficient pressure. However, the magnitude of suction was significantly affected by the lower slope of angle as the highest maximum recorded suction coefficient is (-1.62) for the 5° overhang roof house. Results also showed that at higher slope angle, the 15° overhang roof house recorded a significant drop in suction values where the lowest maximum suction coefficient (-0.02) happens at Zone B. As such, the introduction of small degrees slopes can be one of the factors that contribute to the damage of the low-rise house when subjected to strong wind.